2012
DOI: 10.1371/journal.pone.0051209
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal Range of Anopheles sinensis in Yongcheng City, China by Mark-Release-Recapture Methods

Abstract: BackgroundStudying the dispersal range of Anopheles sinensis is of major importance for understanding the transition from malaria control to elimination. However, no data are available regarding the dispersal range of An. sinensis in China. The aim of the present study was to study the dispersal range of An. sinensis and provide the scientific basis for the development of effective control measures for malaria elimination in China.Methodology/Principal FindingsMark-Release-Recapture (MRR) experiments were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The overall recapture rates of the marked flown and unflown BPHs in our MRR experiments in the paddy field were 9.60% and 0.92%, respectively. MRR studies on moths and midges were reported to have low recapture rates [3031], which is in accordance with our results. These recapture rates were low compared with those reported in other insect dispersal studies that used the MRR method, e.g., 10.1% to 13.4% in a report on leafhoppers on sugarcane plants [24].…”
Section: Discussionsupporting
confidence: 92%
“…The overall recapture rates of the marked flown and unflown BPHs in our MRR experiments in the paddy field were 9.60% and 0.92%, respectively. MRR studies on moths and midges were reported to have low recapture rates [3031], which is in accordance with our results. These recapture rates were low compared with those reported in other insect dispersal studies that used the MRR method, e.g., 10.1% to 13.4% in a report on leafhoppers on sugarcane plants [24].…”
Section: Discussionsupporting
confidence: 92%
“…As noted in the literature, the flying distance of different types of mosquitoes can be kilometers, under advantageous geographical, wind velocity, and other meteorological conditions. 129 , 130 The assumption was set such that the highest risk occurs within 5,000 m between imported cases and indigenous cases in a spatial pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have found no significant differences between the survival rates of marked insects to unmarked controls [25-39], others have documented adverse dusting effects [40-47], with factors including brand and colour often associated with dramatic differences between marked and unmarked controls.…”
Section: Discussionmentioning
confidence: 99%